Knowledge and Attitude of People in Simunjan, Sarawak Regarding Rainwater Harvesting System (RWH) as Water Resource Alternative: Pengetahuan dan Sikap Penduduk Simunjan, Sarawak Terhadap Sistem Penuaian Air Hujan (SPAH) Sebagai Bekalan Air Alternatif - Saleh, Yazid; Sulaiman, Siti Nur Eliza; Mahat, Hanifah; Hashim, Mohmadisa; Nayan, Nasir; Anuar Ghazali, Mohamad Khairul (Journal of Techno-Social, 2022)
This article aims to examine the knowledge and attitude of the people of Simunjan, Sarawak towards the Rainwater Harvesting System (SPAH) as an alternative air preparation in the area. For the purposes achieved, quantitative quantities with the designs that have been used in this study. Study data were obtained using questionnaire instruments and supported using the library method. A total of 341 respondents among the residents of Simunjan, Sarawak consisting of residents of Kampung Nanas, Kampung Kelka and Kampung Sageng were selected as the study sample. Data were analyzed using descriptive analysis (frequency, percentage, mean and standard deviation) and Pearson correlation analysis. The findings showed that the level of knowledge (M = 3.73, SP = 0.31) and attitude (M = 3.76, SP = 0.40) were at a high level. Meanwhile, Pearson correlation analysis showed a significant strong relationship between knowledge and population attitudes towards the use of SPAH r = 0.748, p